IFC Mobile Money Study 2011 : Brazil - International Finance Corporation (Washington, DC, 2015)
Although a number of m-money businesses have emerged around the world, few have reached significant scale. Overall, m-money uptake is limited when contrasted with its apparent promises of reaching the unbanked and underserved, of servicing existing banking clients, and of being a means for a cashless society. This study examines the following in more detail: existing major money flows and the critical mass of low-value, high-volume payment transactions and whether m-money can be used for them (i.e., potential demand); regulatory environment and major obstacles for m-money uptake; business models of partnering institutions; payment behavior of users and nonusers (banked and unbanked), in particular where they receive funds and how they use money, including alternative means; and existing and potential agents networks, their requirements to run m-money as a viable business, and their training needs. This report provides detailed information regarding the five main topics as they relate to Brazil, business models, money flows and demand, potential user perceptions and behavior, regulation, and agent networks.